Make Every Minute Count - Haynes, Marion E. (New Delhi Kogan Page, 2000)
Each of us manages time differently to suit our own personality and lifestyle, but the basic processes are described here, so we can choose which to apply to our circumstances.
Keywords: Executives--Time management -- Time management